2018
DOI: 10.15520/ijcrr/2018/9/09/600
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Physico-Chemical Properties of Water on the Compressive Strength of Concrete

Abstract: Objective: To determine the influence of the physico-chemical compositions of the different sources of water on the compressive strength of concrete. Materials and Methods: Seventy-two 150mm x 150mm concrete specimen were cast using six different sources of water and cured using the same water sources by immersion for 7, 14, 21 and 28 days. Each water sample was used to produce 12 specimen, three each for the four different ages. Concrete cubes were weighed using digital weighing machine before testing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The pH of seawater used for curing concrete test specimens was also 8.56. It is essential to measure the pH of seawater before the curing process (Akomah & Jackson, 2018;Al Jaaf et al, 2019), as shown in Figure 3.…”
Section: Ph Of Seawater Curingmentioning
confidence: 99%
“…The pH of seawater used for curing concrete test specimens was also 8.56. It is essential to measure the pH of seawater before the curing process (Akomah & Jackson, 2018;Al Jaaf et al, 2019), as shown in Figure 3.…”
Section: Ph Of Seawater Curingmentioning
confidence: 99%
“…In recent years, the attention of researchers has been drawn to the fact that the properties and quality of various materials can be determined not only by the quality of chemicals, but also by their physical and chemical properties [16]. In addition, in area of pharmacy it was shown that the quality of the final product (drug in this case) obtained as a result of local interaction of different starting materials depends not only on the quality of the main materials, but also on the physical and chemical properties of materials and substances that play the role of fillers, previously considered chemically inert [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the quality of the water used is determined by the relevant standards, the list of controlled physico-chemical indicators of the quality of water used for hydration of cement in the production of concrete is not fully defined. There is no division of water into groups that differ in indicators of key physical and chemical properties [2,3,16]. This is paradoxical, but the influence of the physical and chemical properties of water involved in the process of hydration of cement on the strength of concrete has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%